Pemikiran Ibu Nyai HJ. Khoiriyah Hasyim Tentang Pendidikan Perempuan - Iswari Maghfiroh, Dana; Mahadun , Hanifuddin (TABYIN: JURNAL PENDIDIKAN ISLAM, 2024)
Discrimination against women, especially in education, was prevalent in the past. Ibu Nyai Hj. Khairiyah Hasyim, a daughter of NU founder KH. Hasim Asy’ari, was committed to overcoming backward thoughts related to women's education. This research focuses on Ibu Nyai Hj. Khairiyah Hasyim's thoughts on women's education. This qualitative literature study employs a descriptive data analysis approach. Data collection involves literature review relevant to the topic. Subsequently, data are reduced, analyzed, and conclusions are drawn based on the research focus. The findings reveal that Ibu Nyai Khairiyah Hasyim's concept of women's education includes: First, the absence of a dichotomy between male and female education. Second, women should be independent and not solely reliant on men. Third, women as Madrasatul Ula should think critically and excel in socialization with a solid foundation in religious knowledge. These concepts are then implemented in the curriculum at Pesantren Seblak, focusing on skills development as a means of empowering women in education